Pengaruh Media Annotated Illustrations dan PhET terhadap Prestasi Belajar Fisika Siswa - Laxmi Zahara; Sapiruddin Sapiruddin; Fartina Fartina; M. Ari Zapri (Universitas Hamzanwadi, 2022)
The presence of media in the learning process acts as a tool to prevent communication failures between teachers and students. This study aims to determine the effect of Annotated Illustration and PhET media on physics learning achievement on Dynamic Electricity material. The research method used in this study is a quantitative research method. While the type of research is experimental research. In this study, the PhET media was applied to the experimental class, while the Annotated Illustrations media was applied to the control class. The calculation results obtained = 3.836 and = 2.056 at a significant level of 5% and dk = 1 + 2. Therefore > , so that the null hypothesis (H0) is rejected or the alternative hypothesis (Ha) is accepted, which means that there is a difference in the effect of Annotated Illustrations and PhET on physics learning achievement on Dynamic Electricity material.